(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Foreign DirectInvestment (FDI) is considered to be the lifeblood of economic developmentespecially for the developing and underdeveloped countries. Multinationalcompanies (MNCs) capitalise on foreign business opportunities by engaging inFDI, which is investment in real assets (such as land, buildings, or existingplants) in foreign countries. MNCs engage in joint ventures with foreign firms,acquire foreign firms, and form new foreign subsidiaries. It plays an importantrole in the long-term development of a country not only as a source of capitalbut also for enhancing competitiveness of the domestic economy through transferof technology, strengthening infrastructure, raising productivity andgenerating new employment opportunities (Deutsche Bundesbank, 2003). MNCs areinterested in boosting revenues through FDI by attracting new sources ofdemand, entering into profitable markets and exploiting monopolisticadvantages. Currently these corporations are increasingly establishing overseasplants or acquiring existing overseas plants to learn the technology of foreigncountries.